TRANSPLANTASI TERUMBU KARANG UNTUK TUJUAN REHABILITASI DI PANTAI LIPAH - P.S.P. Atmaja; D.B. Wiyanto; I.N.G. Putra; I.P.Y. Darmendra; I.M. Yunarta (Buletin Udayana Mengabdi, 2024)
Indonesia’s coral reefs are known as the most species-rich in the world, but also face exceedingly high levels of local anthropogenic pressure. Reef restoration is likely to play a valuable role in the management of these exceptionally diverse and threatened ecosystems. The transplantation had been conducted in the Lipah Beach with 100 hexagon-shaped structures and 500 coral seeds planted consisted of Acropora spp. and Stylophora spp. During 4 months, the local community also involved in monitoring was carried out once/week to observed the growth rate and survival rate of the transplanted coral seedlings of activity. This study result showed that coral seedlings were successful in growing on transplanted structures with varying growth rates for each species in the range of 0.2 – 0.45 cm/month. Public awareness and massive community involvement in co-management with relevant stakeholders plays an important role for the sustainability of coral reef ecosystem and the associated biota included in it. Keywords: Restoration, Biodiversity, Coral reefs, Hexagon, Community development